Visible Portion of Anterior Teeth at Rest and Analysis of Different Smile Characteristics in the Saudi Population of the Jeddah Region - Mohamed Abdelmageed Awad; Doaa Saleh Alghamdi; Aljawharah Talal Alghamdi (International Journal of Dentistry)
This cross-sectional study aimed to determine the degree of visibility of maxillary and mandibular anterior teeth at rest in different age groups and to evaluate the smile line, smile arc, and number of maxillary teeth displayed during smiling among the Saudi population visiting King Abdulaziz University Dental Hospital, Jeddah, Saudi Arabia. A total of 157 participants (77 males and 80 females) were included in this study with an age range of 19 to 69 years. All participants had maxillary and mandibular anterior teeth without restorations. Crown length and visible portions of anterior teeth at rest were measured using a Fowler Electronic Digital Caliper. Three measurements of each variable were recorded by two independent dental interns and calibrating their measurements was performed. Smile line, smile arc, and number of teeth displayed during smiling were examined. The collected data were statistically analyzed using SPSS software. It was found that the average clinical crown lengths in the maxillary lateral incisor, mandibular central incisor, and canine were significantly higher in males than females. At rest position, females displayed more maxillary central and lateral incisors. The displayed length of maxillary teeth at rest is inversely proportional to increasing age; the reverse occurs in mandibular teeth. The common visibility of maxillary teeth during smiling was from the second bicuspid to its counterpart. Average smile line and consonant smile arc were the most common characteristics. It was concluded that both age and gender affect the characteristics of tooth display at rest and in smiling. These effects should be considered during treatment planning and restoration of anterior teeth to obtain a more predictable esthetic outcome.